Pengembangan Aplikasi Sehatgram Berbasis Smartphone dalam Mengatasi dan Mencegah Obesitas pada Remaja - Romadona, Salsabila (Jurnal Gizi dan Kesehatan Nusantara, 2023)
Adolescence is an important period in the individual development cycle. One of the nutritional problems faced in adolescence is obesity. Riskesdas data in 2018 showed that obese adolescents aged 13-15 years had a prevalence of 11.2%. Obese adolescents aged 16-18 years had a prevalence of 9.5%. In line with technological developments that lead to an easier life, this has the potential to increase cases of obesity, especially in adolescents. This study was aimed to develop the Sehatgram application as a solution to overcome and prevent obesity in adolescents and evaluate the feasibility of the Sehatgram application. The research design was used the Rapid Application Development (RAD) method which consisted of the requirements planning phase, RAD design workshop, and implementation. The assessment of the feasibility of the Sehatgram application was validated by material experts and media experts. The material feasibility assessment got an average score of 4.33 in the "very feasible" category. While the media feasibility assessment got an average value of 4.08 in the "decent" category. There needs to be further improvement of the features in the Sehatgram application that are not yet active and the implementation of Sehatgram for adolescents.